2015
DOI: 10.1111/1755-0998.12476
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary evaluation of a genomewide single nucleotide polymorphisms resource generated by RAD‐seq for the small yellow croaker (Larimichthys polyactis)

Abstract: Recent advances in high-throughput sequencing technologies have offered the possibility to generate genomewide sequence data to delineate previously unidentified genetic structure, obtain more accurate estimates of demographic parameters and to evaluate potential adaptive divergence. Here, we identified 27 556 single nucleotide polymorphisms for the small yellow croaker (Larimichthys polyactis) using restriction-site-associated DNA (RAD) sequencing of 24 individuals from two populations. Significant sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…The relatively high transition/transversion ratio of 2.04 after filtering for paralogs and mitochondrial loci may indicate a bias toward genic regions, as SNPs occur more frequently as transitions in exons than in introns (Park, Yu, Mun, & Lee, 2010). This value may also reflect effective filters to reduce sequencing error in the final SNP dataset (Pujolar et al., 2013; Rašić, Filipović, Weeks, & Hoffmann, 2014; Zhang et al., 2015). Initial examination of the SNP data, prior to filtering, showed many SNPs in the last few base pairs of reads (Figure S2) that may reflect sequencing errors rather than true variants (Pujolar et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high transition/transversion ratio of 2.04 after filtering for paralogs and mitochondrial loci may indicate a bias toward genic regions, as SNPs occur more frequently as transitions in exons than in introns (Park, Yu, Mun, & Lee, 2010). This value may also reflect effective filters to reduce sequencing error in the final SNP dataset (Pujolar et al., 2013; Rašić, Filipović, Weeks, & Hoffmann, 2014; Zhang et al., 2015). Initial examination of the SNP data, prior to filtering, showed many SNPs in the last few base pairs of reads (Figure S2) that may reflect sequencing errors rather than true variants (Pujolar et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that high-throughput sequencing technology provides a novel approach for investigating local adaptation in natural populations of marine fishes 15, 22, 40 . In contrast to previous work that found a lack of genetic structure in populations of S. marmoratus , on the basis of mitochondrial control region sequences and AFLP markers 31 , the most important finding of this study was the detection of the high degree of population differentiation among three sampling sites by using 329 candidate adaptive SNPs (Figs 3b and 5, see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the marine environment is relatively homogeneous compared with freshwater, numerous studies have revealed that differential thermal tolerance may result in ecological adaptation in marine species 5, 20 . Moreover, with the development of sequencing techniques, a growing number of studies using a high number of genome-wide polymorphic makers suggest that marine populations are not as connected as might be presumed 21, 22 . Hence, these techniques allow for inference of neutral population structure and also provide information on local adaptation or speciation events 19, 22, 23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations